Fertility preservation in rare ovarian tumors. Issue 3 (March 2021) - Chelariu-Raicu, Anca; Cobb, Lauren P; Gershenson, David M
Abstract : Although gynecologic cancers usually affect older women, a significant proportion of patients with rare ovarian tumors are of reproductive age. In a young patient who presents with a pelvic mass, a primary consideration should be the probability of a malignancy. If there is any suspicion of a cancer diagnosis, the patient should be referred to a gynecologic oncologist. Key factors in clinical management include assessment of preoperative studies (physical examination, tumor markers, and imaging) to determine the likelihood of a malignancy, appropriate preoperative counseling (including discussion of fertility preservation), choice of surgical approach (minimally invasive vs open), frozen section examination by a gynecologic pathologist, and intraoperative decision making. Fortunately, the clinical features of several rare ovarian tumors are compatible with fertility preservation. These characteristics include a high proportion of stage I disease and unilateral ovarian involvement for most rare histotypes. Once a final diagnosis of a rare ovarian tumor is determined, further clinical management may include the need for further studies, possible referral to a fertility expert, consideration of further surgery (if the initial surgery was incomplete), and recommendations for postoperative therapy. This article reviews the literature on fertility preservation in the context of the treatment of several rare ovarian tumor subtypes, including malignant germ cell tumors, sex cord-stromal tumors, borderline tumors, low grade serous carcinoma, clear cell carcinoma, mucinous carcinoma, and small cell carcinoma of the hypercalcemic type.